2010
DOI: 10.1038/sj.bjc.6605674
|View full text |Cite
|
Sign up to set email alerts
|

The proportion of tumour cells is an independent predictor for survival in colorectal cancer patients

Abstract: BACKGROUND: The proportion of epithelial and stromal cells in tumours is thought to have an important role in the progression of epithelial malignancy. We aimed to determine whether the relative proportion of tumour (PoT) was related to survival in colorectal cancer. METHODS: The PoT at the luminal surface was measured by point counting using virtual tissue sections in a series of 145 colorectal cancer cases. The relationship of PoT to clinicopathological parameters including cancer-specific survival was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
181
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(200 citation statements)
references
References 25 publications
16
181
3
Order By: Relevance
“…These observations corroborate previous findings [4,[6][7][8]10], and thus persist after neoadjuvant chemotherapy.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These observations corroborate previous findings [4,[6][7][8]10], and thus persist after neoadjuvant chemotherapy.…”
Section: Discussionsupporting
confidence: 83%
“…A low TSR in the surgically resected primary tumors was detected in 47% of the patients, a ratio comparable to the latest studies in the literature [4,5] although the initial studies generally indicated a lower frequency (24-29%) of 'low TSR' [6][7][8][9][10]. A possible influence of neoadjuvant chemotherapy on tumor tissue composition may explain, at least partly, this difference.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Nevertheless, we think that it is crucial to investigate all these parameters further (individually or in combination) to assess mCRC patient prognosis: When implementing all these parameters in multivariate analysis for the entire cohort with all clinical standards, such as age, sex, tumor localization, and CEA, the study data revealed that ccfDNA parameters, such as total ccfDNA concentration (P ¼ 0.034; HR, 1.73; 95% CI, 1.04-2.89), as well as BRAF-mutant status (P ¼ 0.002; HR, 7.33; 95% CI, 3.13-25.4), are strong independent prognostic factors. Quantitative analysis of ccfDNA, especially the mA%, preferentially relies on tumor biology, in particular to the proportion and/ or activity of the tumor microenvironment which appears as a significant factor since a low proportion of malignant cells in colorectal cancer is related to poor cancer-specific survival (37). We previously reported the very high variation in mutation load (more than 2,000-fold) among the mCRC patients (35), an observation later confirmed by Bettegowda and colleagues (6).…”
Section: Discussionmentioning
confidence: 56%
“…Such biomarkers could be derived from imaging such as tumour regression grade (TRG) or response of EMVI [53,54]. Alternatively they could be pathological, such as changes in TRG or in tumour cell density (TCD) [55,56], or molecular, such as stratifiers of response to chemotherapy and radiotherapy.…”
Section: Addition Of Nac To Preoperative Treatmentmentioning
confidence: 99%